Oxidative stress: an overview of past research and future insights - Aaser M. Abdelazim; Mosleh M. Abomughaid (All Life, 2024)
‘Oxidative stress' (OS) refers to the deviations in redox biology inside biological systems. This term has been used to illustrate the imbalance between oxidants and antioxidants, which has been a subject of extensive research. The obtained findings suggest that many diseases are linked to OS, including diabetes mellitusinflammation, cancers, autoimmune disorders and neurodegenerative diseases. More recently, significant advances in biochemistry and molecular biology have enabled researchers to find master switches of various OS mechanisms and associate OS development to many biological paradigms. In this review, a brief overview of OS research is provided to offer insight into its future directions. Most importantly, the need for a greater understanding of the OS molecular mechanisms and its vital role in the progression of many disorders is emphasized. Likewise, more work is needed on the utility of reactive oxygen species markers as a diagnostic tool.